Dynamic mechanical behavior of different coral sand subjected to impact loading. (May 2021) - Dong, Kai; Ren, Huiqi; Ruan, Wenjun; Huang, Kui
The mechanical performance of coral sand exhibits significant variation due to the different physical properties of coral sand sampled from individual coral reefs. In this paper, a split Hopkinson pressure bar (SHPB) apparatus is used to conduct impact tests on two types of coral sand to investigate mechanical behavior. Using this approach, compressive stress-strain curves of the one-dimensional strain state are obtained, with strain rates ranging from 460 s −1 to 980 s −1 . The results show that the internal porosity of particles is the main influence factor on strain rate dependency of coral sand subjected to impact loading. Various crushing patterns of the two coral sands will result in different strength performance and friction effects, directly creating variations in the dynamic mechanical properties of moist coral sand. Crushing patterns also have a significant influence on yielding stress and the bulk modulus of the pseudo-elastic response but have little effect on the bulk modulus after yielding. In this paper, the varying dynamic mechanical properties are analyzed on typical brittle coral sand by investigating the dominant crushing pattern of the two sand varieties. The conclusions obtained also provide insight into the strain rate dependency of quartz sand.